MPLEMENTASI KEBIJAKAN PENGELOLAAN PASAR RAKYAT KECAMATAN PASAN Di KABUPATEN MINAHASA TENGGARA - KOTANGON, FRICILIA; Rares, Joyce Jacinta; Tampongangoy, Deysi (JURNAL ADMINISTRASI PUBLIK, 2018)
Abstrack :This research is based on the process of management of Public Market which is not in the order of therule that should be. The policy of Pasan sub-district market management is still constrained by the technicalguidelines of implementation. Not all parties are related to the policy of the People's Market management such asonly some of the implementing parties involved, for example the Department of Trade Industry of Cooperatives ofUMKM and Pasar is involved in the implementation. Utilization of unoptimal market facilities and inadequatemarket facilities. This research is to know the implementation of policy of management of Pasar Rakyat Pasan inRegency of South Minahasa. The theory used is the theory of policy implementation according to Charles O'Jonesnamely, organizing, interpretation, and implementation. The method used is qualitative method with descriptiveapproach. With his instrument as a researcher himself with informants seven people.Data analysis techniques include observation, interviews, and documentation. The results showed that theimplementation of the policy of Pasan Village Market management in South Minahasa Regency has not beenoptimal. This can be seen from the lack of involvement from the parties related to the policy of management ofPasar Rakyat as the implementer so that the implementation of the field is found to be the problem of itsmanagement, such as unsuitable market utilization and limited operational cost so that many facilities andinfrastructures are not fulfilled, garbage, no electricity and clean water. The researcher gives suggestion about thisresearch that is to increase cooperation between field of management of Public Market with implementer of policyof management of Pasar Rakyat in Regency of South Minahasa and Department of Trade Industry of UMKMCooperative and Market must perform its duty not only as executor only but must always monitor and evaluate sothat policy on the run on target.Keywords: Policy Implementation, Management of Public Market.